The Meaning of Fairness in Government Financial Statements: A Phenomenology Study - Ridwan, Ridwan; Indriasari, Rahayu; Mayapada, Arung Gihna; Djalil, Novita Muliyani; Jurana, Jurana; Parwati, Ni Made Suwitri (Universitas Syiah Kuala, 2021)
Objective This study aims to investigate the meaning of fairness in government financial statements in Indonesia local governments.Design/methodology The qualitative method with phenomenology as an analysis tool was used in this research. Research data was obtained through observation and in-depth interviews. Regional Government of Tojo Una-Una Regency, Indonesia, was identified as research subject while informants consist of the Regional Revenue Agency (Secretary and Treasurer) as the compiler of the regional government financial statements, inspectorate as the auditor, and the general public.Results The result of this study reveals that the fairness of the government financial statements is interpreted as the suitability of the government financial statements with the law, which is oriented to the actions results by ignoring the process that must be passed. It was also found that the fairness of government financial statements is interpreted as being free from prejudice on complaints if fraud is found on the financial statements.